Pengaruh Country of Origin dan Celebrity Endorser Terhadap Keputusan Pembelian Smartphone Vivo Melalui Citra Merek Sebagai Variabel Intervening (Studi Kasus Pada Mahasiswa Universitas Sarjanawiyata Tamansiswa) - Bagas Ponco Kinasih (JURNAL EKOBIS DEWANTARA, 2020)
This study aims to determine (1) the influence of country of origin on brand image (2) the influence of celebrity endorser on brand image (3) the influence of country of origin on purchasing decisions (4) the influence of celebrity endorser on purchasing decisions (5) the influence of brand image on buying decision. In this study the population was 100 students from Sarjanawiyata Tamansiswa University, Yogyakarta VIVO smartphone users. The data collection method uses a questionnaire method that is distributed using the Accidental Purposive Sampling technique. Whereas the T test technique and classic assumptions consisting of normality test, multicollinearity test, and heterokesdasticity test. The results showed that the country of origin variable influenced the brand image, celebrity endorser affected the brand image, country of origin did not affect the purchasing decision, celebrity endorser did not affect the purchasing decision, brand image influenced the purchasing decision.